Metal contamination and human health risk associated with the consumption of Labeo rosae from the Olifants River system, South Africa. Issue 2 (27th May 2016) - Lebepe, J; Marr, SM; Luus-Powell, WJ
Abstract : The Olifants River, a tributary of the Limpopo River system, is one of the most polluted rivers in South Africa. In May 2011 the concentrations of metals in fish muscle tissue from two impoundments, Loskop and Flag Boshielo dams, on the Olifants River were measured and a human health risk assessment conducted to investigate whether it was safe to consume Labeo rosae from these impoundments. Labeo rosae is one of the most common pan fish in these impoundments and is readily available to rural communities. Metals are accumulating in the muscle tissue of L. rosae even although the fish populations appear to be healthy. At Loskop Dam all L. rosae analysed exceeded the recommended hazard quotient (HQ) of 1 for antimony, and less than 50% exceeded that for lead. At Flag Boshielo Dam, the recommended HQ was exceeded for lead in less than 50% of L. rosae analysed, and more than 50% exceeded that for antimony. The weekly consumption of 150 g of L. rosae muscle tissue from these impoundments may pose an unacceptable health risk to rural communities.